Bells, auspiciousness and the god of music: reflections on sound in ritual space in Nepalese Hindu traditions - Zotter, Astrid (Worship sound spaces, 2020)
In Nepal, as elsewhere in South Asia, many rituals performed in public or private space feature sound and music. The rich repertoire of musical traditions
Gesehen am 15.04.2021